Analysis of the Productivity of Garden Maintenance Work and Efforts to Improve Effective and Efficient Work Procedures - Eriansyah; Noorhamsyah; Dadang Ruchyat; Sofyan Bulkis; Herijanto Thamrin; M Atta Bary (Jurnal Loupe, 2024)
Weeds growing wild among the staple crops cultivated by farmers have become a serious problem and must be immediately controlled, especially in forestry, agricultural and plantation areas. Therefore, practical knowledge is needed about how to manage the problem of weeds that grow undesirable and how to overcome them. Non-chemical weed control is carried out with physical activity. Physical activity carried out by workers while working is a physical workload that will affect their work productivity. The weight or lightness of work done by workers can be measured through direct measurements of human limbs or physique, among others, heart rate, blood pressure, body temperature, sweat rate, consumption of inhaled oxygen and chemical content in the blood. This study aims to identify the use of semi mechanical weed tools and brush cutter as well as analyze the physical workload experienced by workers. The stages and methods of research are carried out by measuring and testing tools in the field based on technical aspects including theoretical work capacity, effective work, field efficiency, fuel consumption, while ergonomic work aspects by measuring workload and fatigue levels directly on the operator's heart rate. From the measurement and calculation of the Increase Ratio of Heart Rate (IRHR), the lowest workload level was obtained with an index of 1.15 and the highest workload level of 1.51.